2022
DOI: 10.1523/jneurosci.2139-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin-Releasing Peptide Contributes to Stress-Related Mood Disorders and Inhibits Sleep/Mood Regulatory Melanin-Concentrating Hormone Neurons in Rats

Abstract: Stress disorders impair sleep, quality of life, however, their pathomechanisms are unknown. Prolactin-releasing peptide (PrRP) is a stress mediator, therefore, we hypothesised that PrRP may be involved in the development of stress disorders. PrRP is produced by the medullary A1/A2 noradrenaline (NA) cells, which transmit stress signals to forebrain centers, and by non-NA cells in the hypothalamic dorsomedial nucleus. We found in male rats that both PrRP and PrRP-NA cells innervate melanin-concentrating hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 84 publications
1
1
0
Order By: Relevance
“…Vas et al’s latest animal study found that PrRP plays a critical role in regulating sleep and affective states, and normal PrRP signaling appears to protect Wistar rat models from stress-induced damage. However, persistent sleep deprivation can lead to overactivation of PrRP cells and depletion of PrRP protein and receptors, 36 which is consistent with the findings of this study. Due to the anterior pituitary, PRL secretion is regulated by a variety of other modalities in addition to being stimulated by hypothalamic prolactin-releasing hormone.…”
Section: Discussionsupporting
confidence: 91%
“…Vas et al’s latest animal study found that PrRP plays a critical role in regulating sleep and affective states, and normal PrRP signaling appears to protect Wistar rat models from stress-induced damage. However, persistent sleep deprivation can lead to overactivation of PrRP cells and depletion of PrRP protein and receptors, 36 which is consistent with the findings of this study. Due to the anterior pituitary, PRL secretion is regulated by a variety of other modalities in addition to being stimulated by hypothalamic prolactin-releasing hormone.…”
Section: Discussionsupporting
confidence: 91%
“…Tissue homogenates of the large brain regions all contained PrRPR mRNA, except for the midbrain [196]. Expression of PrRPR mRNA was detected in the dorsal hypothalamic area and LHA in postmortem human hypothalamic samples via RT-PCR [190].…”
Section: Distribution Of Prrp Receptorsmentioning
confidence: 96%
“…PrRP fibers primarily target the HTH [181], which is probably also the case in humans [188] and suggests functions in homeostatic regulation. The most densely innervated areas are the PVN, the DMN, the perifornical area, and the LHA [130,177,189,190]. Several hypothalamic areas receive moderate PrRP innervation, such as the anteroventral periventricular area (AV3V), the magnocellular nuclei, and the PeN, including the ependymal layer.…”
Section: Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Miklos' current research working with collaborators across the globe includes the characterization of the human brain (g)lymphatic system (Mezey and Palkovits, 2015;Mezey et al, 2021), identifying SARS-CoV-2 entry sites into the human brain (Vitale-Cross et al, 2022), identifying the role of neuropeptides and their signaling in neuropsychiatric disorders (Barde et al, 2016(Barde et al, , 2024Hökfelt et al, 2018;Zhong et al, 2022;Samardžija et al, 2023;Vas et al, 2023), and neurogenetics (Roy et al, 2017;Dóra et al, 2022;Hardwick et al, 2022).…”
mentioning
confidence: 99%